Comparação do perfil proteico de espermatozoides em diferentes espécies - Silvino, Mariana Baraldi Silva (2018)
Proteins present in seminal plasma of domestic animals present several functions in sperm physiology, acting in capacitation processes, acrosome reaction, interaction between gametes and sperm protection. Thus, the present study characterized proteins present in sperm cells from sheep, goats, horses, pigs and dogs. By means of mass spectrometry, a total of 128 proteins were identified in the enriched fraction of spermatozoa of the species used. From this total, identified proteins were found in all species, however six proteins were present in four of the five species studied: angiotensin-converting enzyme, ATP synthase subunit, hexokinase 1, malate dehydrogenase, pyruvate dehydrogenase, succinyl- CoA and a total of 14 proteins were identified in at least 3 species. This study was the first to characterize the proteins present in the enriched fraction of spermatozoon of dogs, in addition to comparing five species. Despite the high similarity between some species, the spermatozoid presents protein differences in its composition, which could explain the different variations in the fertilization process.